Trait transference from brands to individuals: The impact of brand-behavior congruency - Jerónimo, R.; Ramos, T.; Ferreira, M. B. (Journal of Business Research, 2018)
Consumers' strategic use of brands as a way of influencing the impressions others have about them is buttressed by research showing that brand personality traits may carry over and affect perceptions about their users or endorsers. However more often than not brand users engage in all sorts of trait-implying behaviors that may sometimes be in conflict with the brand personality. In two studies we explored how perceivers integrate these two sources of information when creating first impressions of brand users. Results indicated that when traits associated with brands and the users' trait-implying behaviors were in conflict, brand trait transferences were inhibited, whereas traits inferred from the behaviors were enhanced. These findings concerning brand trait transference inhibition and trait inference enhancement may provide new insights on how brand personality influences perceptions about their users, with distinctive consequences for marketing strategy.